Thai reference grammar - Noss, Richard B. (Middletown, DE, 2019)
Thai, or more precisely Siamese or Central Thai, is the national and official language of Thailand and the native language of the Thai people and Thai Chinese. Thai is a member of the Tai group of the Tai–Kadai language family. Over half of the words in Thai are the amalgamation of Pali, Sanskrit and Old Tai-Mon-Khmer language. It is a tonal and analytic language. Thai also has a complex orthography and relational markers. Thai is mutually intelligible with Lao.This reference grammar was developed by the US Foreign Service Institute to help diplomats learn the language. The Thai script is not used as the focus is on the spoken language.